2016
DOI: 10.1177/0269881116667709
|View full text |Cite
|
Sign up to set email alerts
|

Subanesthetic ketamine decreases the incentive-motivational value of reward-related cues

Abstract: The attribution of incentive-motivational value to reward-related cues contributes to cue-induced craving and relapse in addicted patients. Recently, it was demonstrated that subanesthetic ketamine increases motivation to quit and decreases cue-induced craving in cocaine-dependent individuals. Although the underlying mechanism of this effect is currently unknown, one possibility is that subanesthetic ketamine decreases the incentive-motivational value of reward-related cues. In the present study, we used a Pav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 62 publications
(90 reference statements)
0
12
0
Order By: Relevance
“…Several studies demonstrated anti-depressant and anti-addiction properties of ketamine. One study suggested that ketamine may be used to treat addiction by decreasing the incentive-motivational value of reward-related cues [20]. Other studies have shown a prolongation of abstinence from the use of alcohol and heroin in dependent individuals [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrated anti-depressant and anti-addiction properties of ketamine. One study suggested that ketamine may be used to treat addiction by decreasing the incentive-motivational value of reward-related cues [20]. Other studies have shown a prolongation of abstinence from the use of alcohol and heroin in dependent individuals [21].…”
Section: Discussionmentioning
confidence: 99%
“…First, this study focused on the prehospital setting, and was therefore limited in its capacity to assess whether the use of ketamine may lead to dependence or addiction. However, research has reported the anti-addiction property of ketamine [ 20 - 22 ]. A prospective cohort study with a longer follow-up period is warranted to verify the anti-addiction property of ketamine reported by the research community.…”
Section: Discussionmentioning
confidence: 99%
“…Together our findings that account for behavior based on tracking tendency suggest that BLA-IC is necessary for supporting the initial approach directed at the preferred response location. Yet the modest effects for both food cup and lever approach behaviors suggests other brain circuits support these behaviors in the absence of BLA-IC communication (Flagel, Clark et al 2011, Saunders and Robinson 2012, Clark, Collins et al 2013, Saunders, Yager et al 2013, Chang, Todd et al 2015, Haight, Fraser et al 2015, Ahrens, Meyer et al 2016, DiFeliceantonio and Berridge 2016, Fitzpatrick, Creeden et al 2016, Fraser, Haight et al 2016, Naeem and White 2016, Sculfort, Bartsch et al 2016, Stringfield, Palmatier et al 2016, Torres, Glueck et al 2016, Versaggi, King et al 2016, Fitzpatrick and Morrow 2017, Koshy Cherian, Kucinski et al 2017, Pitchers, Phillips et al 2017, White and Naeem 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Pavlovian conditioned approach: procedure. Pavlovian conditioned approach was performed as previously described 82,83 . For two days prior to pretraining, rats were familiarized with banana-flavored food pellets (45 mg; Bioserv; Frenchtown, NJ) in their home cages (25 pellets/cage).…”
Section: Animalsmentioning
confidence: 99%